Magnetic Modular Robotics: An Educational Approach to Robot Competitions - Antunes, Bruna G.; Bezerra, Luiz F. F. P.; Canella, André L. C.; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This research presents the design and implemen-tation of a modular robotic platform for educational purposes, based on the mini sumo competition modality. The developed robot consists of magnetically connectable modules that sim-plify both mechanical and electrical integration, eliminating the need for exposed wiring and reducing setup complexity. The platform is based on an Arduino Nano microcontroller, supporting infrared and ultrasonic sensors. It features a modular structure with magnetic alignment and Schottky-based Graetz bridge protection, which helps prevent damage caused by po-larity reversal. The created platform demonstrates modularity, robustness during reconfiguration, and effective operation in sumo competition environments. The proposed solution enhances STEM engagement by enabling rapid prototyping, sensor exper-imentation, and iterative control strategies in hands-on learning settings.